Crystal structures of ordered and plastic-crystalline phases of iso-butyllithium by X-ray powder diffraction12. Issue 76 (7th September 2018) - Bodach, Alexander; Fink, Lothar; Schmidt, Martin U.
Abstract : The crystal structures of solid, donor-free i-BuLi at different temperatures were determined from X-ray powder diffraction data. Abstract : Donor-unsupported iso-butyllithium consists of hexamers with an ordered triclinic structure at −80 °C (α-phase). At ambient temperature, the compound exists as an orthorhombic, remarkably stable, plastic-crystalline γ-phase, which is built by disordered hexamers adopting a distorted face-centred cubic packing. Both structures were determined by X-ray powder diffraction. Additionally, an intermediate β-phase is observed.